EDUKASI NEUROPATI DIABETIK PADA LANSIA DENGAN DIABETES MELLITUS DI POLIKLINIK GERIATRI RUMAH SAKIT TK II UDAYANA - Dewi, Triyana Puspa (STIKES Advaita Medika Tabanan, 2025)
Diabetic neuropathy is a common complication that may be experienced by diabetes patients, especially the elderly. Advancing age is one of the factors that can lead to an increased incidence if accompanied by inconsistent blood pressure and blood sugar control. The occurrence of diabetic neuropathy takes a considerable amount of time before symptoms appear. Symptoms such as tingling, cramps, and burning are often overlooked, even though they are early signs of peripheral neuropathy in the limbs that need to be watched out for. Elderly individuals with diabetes need to recognize neuropathy so they can prevent these complications. Community service activities were carried out by providing education on the definition, types of neuropathy, risk factors, signs and symptoms, detection, and management. The activity was attended by 34 elderly individuals who underwent examinations at the Geriatric Polyclinic of RS Tk II Udayana. The elderly were also taught how to recognize neuropathy with a simple examination, namely the Ipswich test technique. The evaluation was conducted by asking three questions related to neuropathy, and the elderly were able to provide the correct answers.